VD_FINDINFO AP / 2009 / 211 vom 19. September 2008 - VD Tribunal cantonal (2008)
MOYEN DE DROIT CANTONAL, RECOURS EN NULLITÉART. 68 OJ, APPRÉCIATION DES PREUVES | 4 CPC, 444 al. 1 ch. 3 CPC, 444 al. 1 CPC, 444 al. 2 CPC